The microscopic threat with a macroscopic impact: Microplastics along the southeast Florida reef tract. (June 2023) - Wightman, Emma; Renegar, D. Abigail
Abstract: Microplastics decrease oceanic water quality and negatively impact marine life. This research quantified and classified marine plastic pollution along the Southeast Florida Reef Tract (SEFRT) to estimate the risk of microplastic damage to corals in this region. Surface and bottom water samples were collected at seven sites along the SEFRT over the course of six months and were analyzed for microplastic content. FTIR spectrophotometry was used to evaluate microplastic composition. Overall, seven plastic polymers were found across a total of 1204 microplastic items. Five contaminants were also identified, indicating that microplastics may be congregators of these hazardous contaminants. Significantly more total plastics were found in surface samples than in bottom samples, but plastic quantities were not significantly different when month, depth, and location were combined. Plastics were determined to have entered the ocean from multiple sources; in order to protect vulnerable reef ecosystems in this area, a two-factor approach is necessary to halt the release of microplastics into the ocean, including widespread plastic clean-up efforts and improvements to plastic waste management. Highlights: Microplastic pollution is abundant along the Southeast Florida Reef Tract—over 1200 individual microplastic items were found. Plastic pollution is homogenous between depth, location, and time of year combined along the SEFRT. Microplastic items found in surface water samples were significantly higher than bottom water samples. Contaminants were found in association with microplastics. A multi-faceted approach is necessary to prevent further accumulation of plastic pollution in the ocean.